Biased Wage Expectations and Female Labor Supply - Maximilian Blesch; Philipp Eisenhauer; Peter Haan; Boryana Ilieva; Annekatrin Schrenker; Georg Weizsäcker (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2023)
Wage growth occurs almost exclusively in full-time work, whereas it is close to zero in part-time work. German women, when asked to predict their own potential wage outcomes, show severely biased expectations with strong over-optimism about the returns to part-time experience. We estimate a structural life-cycle model to quantify how beliefs influence labor supply, earnings and welfare over the life cycle. The bias increases part-time employment strongly, induces flatter long-run wage profiles, and substantially influences the employment effects of a widely discussed policy reform, the introduction of joint taxation. The most significant impact of the bias appears for college-educated women.
Keywords: D63; H23; I24; I38; J22; J31; 330; returns to experience; biased beliefs; part-time work; dynamic life-cycle models